2019
DOI: 10.1155/2019/5821589
|View full text |Cite
|
Sign up to set email alerts
|

Amiselimod (MT-1303), a Novel Sphingosine 1-Phosphate Receptor-1 Modulator, Potently Inhibits the Progression of Lupus Nephritis in Two Murine SLE Models

Abstract: Amiselimod (MT-1303) is a novel and selective sphingosine 1-phosphate receptor-1 (S1P1) modulator with a more favorable cardiac safety profile than other S1P1 receptor modulators. In this study, we evaluated the effects of MT-1303 on the progression of lupus nephritis in two well-known murine systemic lupus erythematosus (SLE) models, MRL/lpr and NZBWF1 mice, compared with those of FK506. Daily oral doses of 0.1 and 0.3 mg/kg MT-1303 not only inhibited the development of lupus nephritis when administered befor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 34 publications
(45 reference statements)
1
10
0
Order By: Relevance
“…Amiselimod (MT-1303), an oral selective S1P 1 receptor modulator, is converted in vivo to its active metabolite, amiselimod phosphate (amiselimod-P), 16 and has a more favorable cardiac safety profile than fingolimod. 17 Our previous findings confirmed that amiselimod inhibits lupus nephritis progression in MRL/lpr and NZBWF1 mice, 18 suggesting its potential effectiveness in the treatment of SLE in humans.…”
Section: Introductionsupporting
confidence: 66%
See 1 more Smart Citation
“…Amiselimod (MT-1303), an oral selective S1P 1 receptor modulator, is converted in vivo to its active metabolite, amiselimod phosphate (amiselimod-P), 16 and has a more favorable cardiac safety profile than fingolimod. 17 Our previous findings confirmed that amiselimod inhibits lupus nephritis progression in MRL/lpr and NZBWF1 mice, 18 suggesting its potential effectiveness in the treatment of SLE in humans.…”
Section: Introductionsupporting
confidence: 66%
“…32 The effects of amiselimod on blood anti-ds-DNA antibody levels in SLE animal models of SLE were contradictory. 18 Administration of amiselimod suppressed the increase in anti-dsDNA antibody levels in MRL/ lpr but not NZBWF1 mice. However, these results are consistent with those observed with other S1P 1 receptor modulators in MRL/ lpr and NZBWF1 mice.…”
Section: Discussionmentioning
confidence: 95%
“…Amiselimod/MT-1303 is an oral prodrug that is converted to its active metabolite (MT-1303-P) by sphingosine kinases (SphKs); it has been evaluated for various immune-mediated diseases such as MS, SLE, IBD, and psoriasis [ 37 , 74 – 77 ]. Amiselimod has a higher affinity for S1PR1 than for S1PR2–5, obtaining a more favorable cardiac safety profile than non-selective S1PRs modulators [ 78 ].…”
Section: S1pr Agonists/modulators In Immunological Disordersmentioning
confidence: 99%
“…Regarding infections, research reveals that only specific subsets are affected, such as T (CD3) and B (CD20) lymphocytes [ 131 , 132 ], whereas natural killer, NKT, granulocyte, and monocyte counts should be not affected, maintaining immune surveillance against cancer and viral infections [ 39 , 134 , 135 ]. Table 2 compares features of S1PR modulators mentioned in this review [ 4 , 39 , 58 , 72 , 74 , 101 , 130 , 133 – 138 ].…”
Section: Positioning S1p Modulators In Ibd: Pros and Consmentioning
confidence: 99%
See 1 more Smart Citation